Lama Perendaman dan Jenis Kertas dalam Ekstrak Mahkota Bunga Malvaviscus penduliflorus sebagai Indikator Asam Basa Alternatif. - Mulyani, Sri, Triastuti Rahayu, S. Si, M.Si (2017)
pH indicator is an essential ingredient in a variety of lab work at secondary schools, especially in the matter of assification substances. Application of natural materials that contain anthocyanins can be used as a natural acid-base indicator. Malvaviscus penduliflorus have anthocyanin in the crown of flowers so that potential as an alternative id-base indicator. This study aims to determine the effect of soaking time and type of paper in the extract of petals Malvaviscus penduliflorus as acid-base indicators. This study using the completely randomized design (CRD), with two treatment factors are the type of paper and the duration of soaking the paper in Malvavicus penduliflorus extract flower crown. Type of paper used was a filter paper and scrap paper soaked in different place with a variety of dipping time of 30 minutes and 40 minutes in the extract of petals lvaviscus penduliflorus. The parameters of the study include oloration of the acid-base indicator paper from extracts of petals Malvaviscus penduliflorus after dipped in acid solution and alkaline. The results showed that the paper pH indicator of extracts of petals Malvaviscus penduliflorus peach color shifts in the acid solution and green in alkaline solution. Long immersion in the paper petals Malvaviscus penduliflorus extract does not affect the color grading papers when dipped in a solution of acid and alkaline. Filter paper has a better ability as a pH indicator, because it gives sharper color gradation when dipped in a solution of acid and alkaline.